Sólitons BPS em um modelo CP(2) calibrado e estendido pela presença de uma impureza magnética - ALMEIDA, Marcos Vinícius Conceição (2023)
We investigated the existence of BPS solitons in two gauged-CP(2) models extended via inclusion of magnetic impurities. Thus, through the implementation of the BPS (Bogomol’nyi-Prasad-Sommerfield) formalism, we observe that the total energy possesses a well-defined Bogomol’nyi bound and a quantized magnetic flux for the topological configu- rations. Further, the analysis verified that the magnetic impurity contributes to the BPS potential and appears in the BPS equation in both models. We then introduce a Gaussian type impurity (which is commonly interpreted as a single barrier/well) for the topological and non-topological cases, and a periodic impurity (a chain of barriers/wells) for the non-topological case only (restricted to the Chern-Simons-CP(2) scenario). Thus, we solve the self-dual equations numerically, according to the boundary conditions corresponding to each case. The resulting solutions present a non-monotonic behavior that inverts the magnetic and electric fields, for the topological case. For the non-topological case, the main effects caused by impurities include a large electrical sector response, with the formation of a periodic profile that spreads to the asymptotics and a multilayered magnetic ring which maintains the magnetic flux confined to the original region in space.